Thievery in rainforest fungus-growing ants: interspecific assault on culturing material at nest entrance - Ronque, M. U. V.; Migliorini, G. H. [UNESP]; Oliveira, P. S. (Springer, 2018)
Cleptobiosis in social insects refers to a relationship in which members of a species rob food resources, or other valuable items, from members of the same or a different species. Here, we report and document in field videos the first case of cleptobiosis in fungus-growing ants (Atta group) from a coastal, Brazilian Atlantic rainforest. Workers of Mycetarotes parallelus roam near the nest and foraging paths of Mycetophylax morschi and attack loaded returning foragers of M. morschi, from which they rob cultivating material for the fungus garden. Typically, a robbing Mycetarotes stops a loaded returning Mycetophylax, vigorously pulls away the fecal item from the forager's mandibles, and brings the robbed item to its nearby nest. In our observations, all robbed items consisted of arthropod feces, the most common culturing material used by M. parallelus. Robbing behavior is considered a form of interference action to obtain essential resources needed by ant colonies to cultivate the symbiont fungus. Cleptobiosis between fungus-growing ants may increase colony contamination, affect foraging and intracolonial behavior, as well as associated microbiota, with possible effects on the symbiont fungus. The long-term effects of this unusual behavior, and associated costs and benefits for the species involved, clearly deserve further investigation.
Keywords: Ant behavior; Fungus-growing ants; Interference competition; Theft; Atlantic rainforest